Expresión xyz∨xy¬z∨¬xyz
El profesor se sorprenderá mucho al ver tu solución correcta😉
Solución
Solución detallada
(x∧y∧z)∨(x∧y∧¬z)∨(y∧z∧¬x)=y∧(x∨z)
y∧(x∨z)
Tabla de verdad
+---+---+---+--------+
| x | y | z | result |
+===+===+===+========+
| 0 | 0 | 0 | 0 |
+---+---+---+--------+
| 0 | 0 | 1 | 0 |
+---+---+---+--------+
| 0 | 1 | 0 | 0 |
+---+---+---+--------+
| 0 | 1 | 1 | 1 |
+---+---+---+--------+
| 1 | 0 | 0 | 0 |
+---+---+---+--------+
| 1 | 0 | 1 | 0 |
+---+---+---+--------+
| 1 | 1 | 0 | 1 |
+---+---+---+--------+
| 1 | 1 | 1 | 1 |
+---+---+---+--------+
(x∧y)∨(y∧z)
(x∧y)∨(y∧z)
y∧(x∨z)
Ya está reducido a FNC
y∧(x∨z)